Improvement of Ohmic Contact for InAlGaN/AlN/GaN HEMTs with Recess Etching. Issue 8 (25th March 2018) - Riedmüller, Sandra; Steinmann, Claudia; Grünenpütt, Jan; Scholz, Ferdinand; Blanck, Hervé
Abstract : In this paper, the influence of a recess etching process on the contact resistance and the relevant electrical properties of In0.12 Al0.8 Ga0.08 N/AlN/GaN HEMTs is presented. Without etching, the contact resistance is typically 0.9 Ω mm. By recess etching R cont is reduced to 0.2 Ω–mm. A strong correlation of R cont to the maximum drain saturation current ( I DS+ ) and to the maximum transconductance ( G mMax ) is observed. Devices with R cont of 0.2 Ω mm show I DS+ of 1.7 A mm −1 and G mMax of 620 mS mm −1, respectively. Abstract : To increase device operating frequency device scaling is key and the effect of parasitic resistance becomes important. The contact resistance is the main contributor to the parasitic resistance. The aim of this paper is to optimize the Ohmic contact processing of InAlGaN HEMTs by using the ohm recess technology.